Elevated Body Mass Index is associated with severity of Allergic Rhinitis: Results from a cross sectional study - Alrasyid, Harun; McManus, Alexandra; Mallon, D.; Nicholson, Claire (Moyez Jiwa, 2008)
Background: Allergic rhinitis is a prevalent chronic respiratory problem that can impair quality of life, sleep and work. The increase in the prevalence of allergic rhinitis among the general population appears to have an association with weight. Obese individuals are more vulnerable to allergy. Since obesity appears to be linked with the occurrence of allergic rhinitis, it is hypothesized that obesity also has an influence on the severity levels of allergic rhinitis. This study was designed to investigate the patterns and severity of allergic rhinitis patients, determine the prevalence of obesity in patients with allergic rhinitis, examine the association between the severity of allergic rhinitis and body mass index, and develop recommendations for further research.